ASSESSING THE LEVEL OF A TRIAL NATRIURETIC PEPTIDE AND SOME BIOCHEMICAL PARAMETERS IN MEN WITH TYPE 2 DIABETIC NEPHROPATHY - AL-FATLAWI, HAWRAA YOUSIF; JWAD, SAHER MAHMOOD (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
The Aim: The current study is conducted to diagnose the relationship between ANP levels and diabetic nephropathy, the applicability of adopting it as a biomarker or an early index to prevent renal failure. Study Design: The current study estimates the levels of atrial natriuretic peptide and some biochemical parameters in healthy subjects and patients with type 2 diabetes. Place and Duration of Study: The study duration was from 1/3/2021 to 1/10/2021. The patients were divided into several groups based on their age, diabetic duration, albumin to creatinine ratio (ACR) and glomerular filtration rate. Methodology: It determines the possibility of adopting these levels in diagnosing the progression of diabetic nephropathy. The study also included a follow-up of (60) men with type 2 diabetes who were attending the Diabetes and Endocrinology Center of Al-Sadr Medical Hospital in Najaf, as well as (15) men from the Dialysis Center of the same hospital, and (15) healthy men as a control group, their ages were (30-80) years. Results: The trial showed a significant effect (P<0.05) for age groups and diabetic duration on the levels of atrial natriuretic peptide, cystatin C, amyloid A, serum creatinine, albumin to creatinine ratio in urine, and glomerular filtration rate. However, no significant differences (P>0.05) were observed in the albumin level in serum. Moreover, the results showed a noticeable increase (P<0.05) in the levels of atrial natriuretic peptide, cystatin C, amyloid A, creatinine in serum and glomerular filtration rate with an increase in albuminuria. Conclusion: A significant increment was indicated by the results reading (P<0.05) in the levels of atrial natriuretic peptide, cystatin C, amyloid A, creatinine in serum and the ratio of albumin to creatinine with the progression of the stages of diabetic nephropathy.